THE EFFECT OF E-OFFICE IMPLEMENTATION ON THEEFFECTIVENESS OF PERSONNEL ADMINISTRATIONSERVICES AT THE REGIONAL OFFICE OF THE MINISTRY OF RELIGIOUS AFFAIRS OF WEST SUMATRA PROVINCE - Miftahul Husni; Yulianto Santoso; Irsyad Irsyad; Enceria Damanik (Jurnal Manajemen Pendidikan, 2026)
This study aims to determine the effect of the implementation of the EOffice on the effectiveness of personnel administration services at the Regional Office of the Ministry of Religious Affairs of West Sumatra Province. Method: This research uses a quantitative approach with a correlational design. The population consisted of 168 employees, with a sample of 117 employees selected using proportional random sampling technique. Data were collected through a Likert scale questionnaire and analyzed using descriptive statistics and simple linear regression. Results: The implementation of E-Office and the effectiveness of personnel administration services are in the fairly good category. The analysis results show that the implementation of E-Office has a positive and significant effect on the effectiveness of personnel administration services, with a significance value of 0.000 < 0.05 and a contribution of 83.6% (R² = 0.836). Novelty: This study provides empirical evidence regarding the strong influence of E-Office implementation on the effectiveness of personnel administration services within the Regional Office of the Ministry of Religious Affairs of West Sumatra Province as part of the implementation of government administration digitalization.